УГЛОВАЯ СТРУКТУРА КВАЗАРА 3С47 В ДЕКАМЕТРОВОМ ДИАПАЗОНЕ ВОЛН - Лозинский, А. Б.; Лозинский, Р. А.; Ивантишин, О. Л.; Романчев, Ю. В.; Рашковский, С. Л.; Шепелев, В. А.; Браженко, А. И.; Ващишин, Р. В.; Литвиненко, О. А. (Одеські астрономічні публікації, 2011)
The quasar 3C47 was observed with the URAN network at decameter wavelengths. A model of its angular structure consisting of four components was fitted. Lobes of the source are enlarged significantly in the range if compare with their high frequency dimensions. The hot spots emission is detected at low frequencies but a radio core is disappeared completely due to its flat spectrum.